TVBDs coexistence by leverage sensing and geo-location database - Saeed, Rashid Abdelhaleem; Mokhtar, R.A.; Chebil, Jalel; Hassan Abdalla Hashim, Aisha (2012)
Due to the transition to digital TV (DTV); recently, many countries allow TV white spaces to be used by unlicensed devices. TV White Spaces is considered as an important step towards providing broadband access to millions of digital dividend household around the world and enabling a wide range of innovative wireless devices and services. The key challenge of TV white space systems is to have capabilities to avoid causing harmful interference to licensed services in the TV band as well as unlicensed devices. This requires that TV band devices (TVBDs) must be aware of the presence of each other and with incumbent devices in TV band. Specifically, TVBDs should have the ability to determine whether a TV channel or frequency band is unused before it could transmit. Due to the difficulties associated with sensing and to ensure high protection to broadcaster devices, geo-location database has been proposed recently, where each devices before transmit need to contact the database -at least once per day- and get the idle frequency carrier.